The Role of a Costume as an Artistic Means of Bodily Representation in Contemporary Chinese Sculpture - Song, Yanbo (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article examines the role of costume as an important component of the figurative and expressive system in modern Chinese sculpture. It identifies three main directions in which costume functions as an artistic means: realism, conditional formality, and abstraction. The study concludes that in the artistic language of modern sculpture, costume plays the role of a marker of bodily representation. Depending on the specifics of the artistic task, it acquires either affirmative (modeling of lines, forms and planes of the body) or dialogical connotations (counter-corporeality, expression of the opposition of the natural and the artificial). In the modern repertoire of sculpture, there are alternative ways of interpreting costume as an artistic means and this provides artists with the opportunity to enrich the figurative palette of their works. The role of the costume in the context of realism actualizes artistic imagery beyond the boundaries of the real and the conventional. In this case, the costume acts as a direct continuation of body language. The sculpture of the direction of conventional formality develops between the aesthetics of a dressed moving figure and the image of a person who is cramped in a predetermined physical form. In abstraction, costume operates as part of a symbolic and compositional language, emphasizing symbolism and geometrism and strengthening the system of expressive means, especially texture. Overall, the plasticity of the costume as a means of bodily representation of sculpture enriches the figurative palette of sculpture, allowing body language to play a more active role in the creation of artistic imagery.